2011
DOI: 10.1016/j.ydbio.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Origin and segregation of cranial placodes in Xenopus laevis

Abstract: Cranial placodes are local thickenings of the vertebrate head ectoderm that contribute to the paired sense organs (olfactory epithelium, lens, inner ear, lateral line), cranial ganglia and the adenohypophysis. Here we use tissue grafting and dye injections to generated fate maps of the dorsal cranial part of the non-neural ectoderm for Xenopus embryos between neural plate and early tailbud stages. We show that all placodes arise from a crescent-shaped area located around the anterior neural plate, the pre-plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 96 publications
5
85
0
Order By: Relevance
“…Earlier studies of lineage analysis and spatiotemporal expression of transcription factors during inner ear development led to construction of an inner ear fate map in Xenopus and this fate map allows us to interpret gene expression patterns within the context of the anatomy (8,9). In recent years, genetic and genomic approaches have been developed in Xenopus tropicalis (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Earlier studies of lineage analysis and spatiotemporal expression of transcription factors during inner ear development led to construction of an inner ear fate map in Xenopus and this fate map allows us to interpret gene expression patterns within the context of the anatomy (8,9). In recent years, genetic and genomic approaches have been developed in Xenopus tropicalis (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…These studies showed that sensory placodes arise from a crescent-shaped ectodermal territory surrounding the anterior neural plate at late gastrulation/ early neurulation stages. This contiguous region coincides with the expression domain of transcription factors such as Eya1, Six1/2 and Six4/5, which are crucial for placode formation and are thought to establish a placodal bias in this domain (Lleras-Forero and Streit, 2012;Pieper et al, 2011;Schlosser, 2010). These observations, together with unique properties shared by cells within this territory Martin and Grooves, 2006), argue that it represents the common domain of origin for all placodes, the so-called pan-placodal or pre-placodal region (PPR) Schlosser, 2010;Streit, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Although information is still incomplete in some species about subsets of placodes, a common feature of these fate mapping studies is the initial overlap between the domains of origin of the different placodes (the extent of this overlap has been recently discussed and challenged, for details see Pieper et al, 2011;Schlosser, 2010), which progressively decreases as development proceeds. That is, the precursors of a given placode appear scattered within the PPR domain and partially intermingled with the precursors of adjacent placodes as well as with other ectodermal cells such as epidermal, neural tube or neural crest cells (NCC), and undergo progressive segregation over time, becoming confined to a particular region ( Fig.…”
Section: Initial Segregation and Secondary Coalescencementioning
confidence: 99%
See 2 more Smart Citations